UNDERSTANDING WHY WE GROW OLD AS WE GROW OLDER. (11th November 2018) - Sinclair, D A
Abstract: Artificial intelligence, electric cars, and virtual reality have been touted as the most exciting technologies in the past decade but many researchers believe that, in the next 10 years, advances in human longevity will eclipse them. In cells, there are two main types of information – the digital DNA code and the analog 3D structure of the nucleus governed by the epigenome. Evidence is accumulating that the loss of analog information leading to the scrambling of cell identity is a major cause of aging. If so, it should be possible, not just to forestall the effects of time but actually reverse them. Data supporting this conjecture will be presented, along with an update on human clinical trials and predictions about where the field is going from here.